(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to map research trends on Problem-Based Learning (PBL) in Visual Communication Design (VCD) during 2020–2025 through a Google Scholar–based bibliometric analysis. Bibliographic data were collected using Publish or Perish (PoP) with the query "problem based learning" AND ("visual communication design" OR "visual communication design"), and subsequently analyzed with VOSviewer to generate co-occurrence network, density, and temporal overlay visualizations. The final dataset consists of 200 documents, accumulating 927 citations, with an h-index of 15 and a g-index of 26. Visualization results indicate that dominant nodes are closely associated with applied learning contexts—particularly terms related to VCD and vocational/SMK settings—alongside terms related to learning evaluation and supporting instructional tools, such as outcome assessment (eg, posttest/test) and student activity enhancement. The density map confirms the concentration of terms around these dominant nodes, while the overlay map reveals temporal variation of terms within the visualized year range. Overall, the findings suggest that PBL research at the intersection of VCD captured by this corpus is more strongly oriented toward implementation and pedagogical outcomes than toward deeper conceptual elaboration specific to design reasoning. This study contributes a bibliometric evidence-based map of trends and thematic structure to support state-of-the-art reviews and sharpen future research agendas in PBL–VCD.